In silico study on the allergenicity of underutilized legumes in the Philippines - Usaraga, Julie Dianne D. (College of Home Economics, University of the Philippines Diliman, 2023)
With the current global challenges such as food insecurity, poverty, and climate change, threats to food availability, production, and nutritional security are continuously arising. To effectively address the increasing global food demands, it is imperative to prioritize the cultivation and utilization of underutilized legumes, as they hold immense potential for enhancing food and nutrition security. However, the successful exploitation and utilization of these legumes heavily rely on the existing knowledge regarding them. Therefore, this study aimed to investigate the potential allergenicity of underutilized legumes in the Philippines, specifically Psophocarpus tetragonolobus (winged bean), Lablab purpureus (hyacinth bean), and Phaseolus lunatus (lima bean), through in silico studies. The protein sequences of the storage proteins of the specified legumes were obtained from UniProt, and subsequently analyzed for their potential allergenicity through AlgPred 2.0 and Allermatch. The analysis revealed that all three legumes were potential allergens as they were found to be cross-reactive with other known allergens. Furthermore, only the IgE epitope of Phaseolin was found to be digestible by the enzymes pepsin (with pH 1.3 and >2), chymotrypsin (low and high specificity), and trypsin. Other allergens were found to either have no epitopes or indigestible to the specific gastric enzymes. These underutilized legumes, although they have tremendous potential as food sources, should undergo characterization, specifically regarding their potential allergenicity, before promoting their utilization and commercialization.